The Relevance of Intellectual Call and Entrepreneurship Soul for Welfare Reason of Indonesian Lecturers - Nugroho, Budi Sulistiyo; Sudarmo; Tahirs, Jemi Pabisangan; Komari, Achmad Nur; Afriantoni (The journal of contemporary issues in business and government, 2021)
Our study aimed to identify the relevance of intellectual improvement and jump to entrepreneurship as reasons for extra income for lecturers in Indonesia. The reality in the field is that it is often the case where many individual lecturers in Indonesia have concurrent jobs, between the commitment to become academics for intellectual development idealism and part-time work as individual entrepreneurs in various non-work sectors outside the academic domain. For this fact to be scientifically proven, we conducted a series of data collection, including field observations, a review of national and international publication journals, and other literature that discusses the double standards of the profession for campus intellectuals. Furthermore, we analyze the phenomenological approach and in-depth interpretation to find answers and assumptions to this study’s questions. To simplify this study’s objectives, we chose a qualitative design of the data with the Google Scholar online database and Google search. We talk with keywords, for example, "academic calling,""intellectual enhancement,"entrepreneurial spirit, "additional incomes, "and"Indonesian lecturers. "After conducting in-depth analysis and consideration of other scientific evidence data, it can be concluded that there is a balanced relevance between the desire to remain academic and an intellectual vocation with an entrepreneurial spirit among lecturers and teachers in Indonesia.